MENUMBUHKAN SIKAP SALING MENGHARGAI MELALUI PEMBELAJARAN IPS PADA MATERI BERBAGAI JENIS PEKERJAAN DI SEKITAR KITA - Asti Widiastuti; Hikmatul Ghina; Hilda Fahira; Tin Rustini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In implementing a sense of mutual respect for elementary school students, there are various ways that can be done, namely by providing direct understanding and examples to students. One of them is that in learning activities there is material about various types of work that can help students foster a sense of mutual respect, by providing examples that each job/profession is a good thing to do. However, it is not uncommon for us to find children who do not respect people who they think have a meager job or even see it as a lowly job, therefore we must first show respect for other people.